Tasawuf dan perkembangannya dalam Islam - Simuh (Raja Grafindo Persada, 2002)
ws.c.1/ast c.2/tr, c.3/ast c.4/ir,c.5/wk c.6-10/tr,c.11/ir,c.12/oen, c.13/oen. c.14/tr, c.15-17/oen, c.18/why, c.19-21/eni, c.22/en, c.23-24/wk, c.25